The Phenomenon of “Bondo Nekat” Marriage in Pesantren and Its Impact on Marital Harmony - Rahman, Arif (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
The phenomenon of impulsive marriages, or “bondo nekat” marriages, occurring within pondok pesantren (Islamic boarding schools) has garnered attention due to the frequent lack of thorough preparation and mutual understanding beforehand. The aim of this study is to analyze the impact and determining factors of the success of “bondo nekat” marriage households at Pondok Pesantren Darullughah Wadda’wah. This research employs a descriptive quantitative approach with a field case study method, collecting data through interviews, observations, questionnaires, and documentation, then analyzing it statistically. The findings reveal that most couples marry with minimal financial preparation and are relatively young, yet they can establish harmonious households thanks to religious knowledge, effective communication, and contentment. Despite economic challenges, they maintain happiness and familial harmony, with pesantren experience strengthening conflict management and duty fulfillment. This study contributes significantly to understanding that material readiness is not the sole determinant of marital success, indicating that religious education and moral values play crucial roles in building a sakinah family.